Socio-Economic Assessment of farmer in ‘Kandi’ region of Jammu - Praveen Kumar; S.K. Kher; M. S Nain; P.S. Slathia (Indian Journal of Extension Education, 2018)
The present study was conducted in four districts of Jammu region to find out the socio-personal profile, the awareness regarding various programmes and the various information sources used by the farmers. The findings of the study revealed that more than one third of the respondents were illiterate, agriculture was the occupation of sixty percent of the respondents, 72.50 per cent of the respondent belonged to marginal category having less than one hectare of land. As far as social participation is concerned, 89.32 per cent of the respondents were without membership of any organization. The respondents had a low awareness regarding various programmes. The findings of the study also revealed that among the localite sources, input agencies were the main source of information followed by progressive farmers. Among the personal cosmopolite sources, the Junior Agriculture Assistant was the main source of information followed by Agricultural Extension Officer. Among the Impersonal cosmopolite sources 2.55 per cent got information from newspapers followed by radio and least in order was television.